The help [videorecording (Blu-Ray + DVD)] - Taylor, Tate; Chastain, Jessica, 1977-; Davis, Viola, 1965-; Spencer, Octavia; Howard, Bryce Dallas, 1981-; Janney, Allison; Lowell, Chris, 1984-; O'Reilly, Ahna, 1985-; Spacek, Sissy; Steenburgen, Mary; Stone, Emma, 1988-; Tyson, Cicely; et al. (Touchstone Home Entertainment, 2011)
Mississippi during the 1960s: Skeeter, a southern society girl, returns from college determined to become a writer, but turns her friends' lives, and a small Mississippi town, upside down when she decides to interview the black women who have spent their lives taking care of prominent southern families. Aibileen, Skeeter's best friend's housekeeper, is the first to open up, to the dismay of her friends in the tight-knit black community.